2012
DOI: 10.1371/journal.pone.0030334
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Influence Consulting and Antibiotic Use for Acute Respiratory Tract Infections in Children: A Systematic Review and Meta-Analysis

Abstract: BackgroundRespiratory tract infections (RTIs) are common in children and generally self-limiting, yet often result in consultations to primary care. Frequent consultations divert resources from care for potentially more serious conditions and increase the opportunity for antibiotic overuse. Overuse of antibiotics is associated with adverse effects and antimicrobial resistance, and has been shown to influence how patients seek care in ensuing illness episodes.Methodology/Principal FindingsWe conducted a systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0
13

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(135 citation statements)
references
References 43 publications
4
112
0
13
Order By: Relevance
“…Two reviewers used an extraction form developed for a previous systematic review 10 to independently extract data for study design, setting, patient population, intervention, comparison, outcome(s), and assessment method. Disagreements were resolved by discussion with a third author.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two reviewers used an extraction form developed for a previous systematic review 10 to independently extract data for study design, setting, patient population, intervention, comparison, outcome(s), and assessment method. Disagreements were resolved by discussion with a third author.…”
Section: Resultsmentioning
confidence: 99%
“…10 However, strategies are also needed to help clinicians determine which children are most in need of antibiotics, 11 and reduce inappropriate antibiotic prescribing. 12,13 Given the importance of the parent-clinician interaction in guiding antibiotic use, this study aimed to systematically review the effectiveness of educational or behavioural interventions directed to parents, clinicians, or both, to reduce antibiotic prescribing for children with RTIs in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…Yapılan çalışmalar, eğitimin antibiyotik kullanımı üzerindeki olumlu etkisini kanıtlamıştır ancak süreklilik arz etmelidir. [7][8][9][10][11][12] Halka yönelik eğitim programlarının oluşturulmasında bu konudaki yanlış inanışların, bilgilerin saptanması ve doktor üzerinde antibiyotik reçetelenmesi için baskı oluşturma, önerilen antibiyotiği uygun dozaj ve sürede kullanma ve doktor tavsiyesi olmadan antibiyotik kullanma konularındaki tutumların irdelenmesi gereklidir.…”
Section: Introductionunclassified
“…20,24,25 A recent review demonstrated that, in order to be most effective, interventions to influence parental consulting and antibiotic use should engage children, occur prior to an illness episode, and provide guidance on specific symptoms. 36 While this intervention meets these recommendations, one of the reasons that this program did not influence healthcare behaviour could be that there is already so much information on the internet. Although it was developed with the input of parents, and most parents judged it as clear and complete, the content may not fully connect to the desired information.…”
Section: Discussionmentioning
confidence: 97%